Development of project-based learning electronic student worksheet integrating Ngawi local wisdom to enhance critical thinking skill and environmental caring attitude - Desi Nuzul Agnafia; Qurrotul Anfa (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
PISA 2022 results show the low critical thinking skills of Indonesian students. Previous research in Ngawi also confirmed similar problems with students' critical thinking test scores below 70. This study aims to develop a project-based electronic learner worksheet (PjBL ESW) that integrates Ngawi local wisdom. This research was conducted using the development method or R&D (Research and Development) model of Borg and Gall. Based on data analysis of the results of validation by experts, it shows that the developed PjBL ESW obtained excellent criteria. The T-test results show that PjBL ESW can improve critical thinking skills, with a significance level of 0.000, which leads to the rejection of Ho, which means there is a difference in critical thinking skills between the experimental and control classes. The results of the analysis of the environmental care attitude questionnaire showed an n-Gain of 0.3772, which concluded that the application of PjBL ESW in the Merdeka Belajar curriculum was effective in increasing students' environmental care attitudes related to ecology and biodiversity. The results of this study have an impact on education, especially the research object school, students are motivated, enthusiastic, and active in learning so that the goal of improving critical abilities can be achieved in each student. Local wisdom-based learning brings a new atmosphere for students in familiarizing themselves in loving the environment and developing sustainable principles in preserving the environment.Abstrak. Hasil PISA 2022 menunjukkan rendahnya kemampuan berpikir kritis peserta didik Indonesia. Penelitian sebelumnya di Ngawi juga mengonfirmasi masalah serupa dengan skor tes kemampuan berpikir kritis peserta didik di bawah 70. Penelitian ini bertujuan untuk mengembangkan lembar kerja peserta didik elektronik berbasis proyek (e-LKPD PjBL) yang mengintegrasikan kearifan lokal Ngawi. Penelitian ini dilakukan dengan menggunakan metode pengembangan atau R&D (Penelitian dan Pengembangan) model Borg dan Gall. Berdasarkan analisis data terhadap hasil validasi oleh para ahli menunjukkan bahwa e-LKPD PjBL yang dikembangkan memperoleh kriteria sangat baik. Hasil uji T menunjukkan e-LKPD PjBL dapat meningkatkan keterampilan berpikir kritis, dengan tingkat signifikansi 0,000, yang mengarah pada penolakan Ho, yang berarti ada perbedaan dalam kemampuan berpikir kritis antara kelas eksperimen dan kelas kontrol. Hasil analisis kuesioner sikap peduli lingkungan menunjukkan n-Gain sebesar 0,3772, yang menyimpulkan bahwa penerapan e-LKPD PjBL dalam kurikulum Merdeka Belajar, efektif dalam meningkatkan sikap peduli lingkungan peserta didik terkait ekologi dan keanekaragaman hayati. Hasil penelitian ini membawa dampak bagi pendidikan, khususnya sekolah objek penelitian, peserta didik termotivasi, antusias, dan aktif dalam pembelajaran sehingga tujuan dalam meningkatkan kemampuan kritis dapat tercapai pada setiap peserta didik. Pembelajaran berbasis kearifan lokal membawa suasana baru bagi peserta didik dalam membiasakan diri dalam mencintai lingkungan dan mengembangkan prinsip berkelanjutan dalam melestarikan lingkungan.